Distribución y abundancia de Caiman crocodilus en el Refugio Nacional de Vida Silvestre Caño Negro, Costa Rica - Cabrera Peña, Jorge (2003)
The distribution and abundance of a population of Caiman crocodilus fuscus were estimated by monthly counting of eyeshines at night, from February 1999 to March 2000 in six transects of Río Frío in the Caño Negro National Refuge (RNVSCN), Northern Costa Rica. March was the month with the greatest abundance of caimans observed. The visible fraction of the population (PV2 index) fluctuated between 42.59 % to 54.71 % during the wet season and 35.49 % to 53.93 % in the dry season. The transects of river with greater abundance of caimans were Terrón-Sabogal and Sabogal-Playuela. Significant differences were determined in the abundance of caimans between transects, except the transects Entrada San Sebastían-Las Cubas and Las Cubas-Entrada Caño Los Patos and Entrada Caño Los Patos-Terrón and Boca Sabogal-Playuela. The population of estimated brown caiman in this study was 2283.48 ± 313.5. The statistical analysis by seasons did not show significant differences in the number of caimans observed. Estimated mean number of caimans per km of river was 74.36 /km for 30.7 km of habitat. The results of this study indicated that the fluctuation in population density during the seasons is attributable to local movements.